2017
DOI: 10.1161/circresaha.117.311606
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Macrophage Apoptosis and Atherosclerosis by Lipid-Induced PKCδ Isoform Activation

Abstract: Rationale: Activation of monocytes/macrophages by hyperlipidemia associated with diabetes and obesity contributes to the development of atherosclerosis. PKCδ expression and activity in monocytes were increased by hyperlipidemia and diabetes with unknown consequences to atherosclerosis. Objective: To investigate the effect of PKCδ activation in macrophages on the severity of atherosclerosis. Methods and Results: PKCδ expression and activity were increased in Zucker diabetic rats. Mice with selective deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…A similar finding was reported by Lindau et al, who demonstrated that reduced circulating monocyte levels only affected early lesions but not more advanced atherosclerotic lesions 11 . In the present study, Li et al demonstrated that myeloid cell deficiency in PKCδ indeed increase macrophage proliferation in the atherosclerotic lesion (figure) 4 . The authors could show increases in both BrdU-incorporation and Ki67-staining in PKCδ-deficient macrophages in the atherosclerotic lesion, both which are markers of proliferation.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…A similar finding was reported by Lindau et al, who demonstrated that reduced circulating monocyte levels only affected early lesions but not more advanced atherosclerotic lesions 11 . In the present study, Li et al demonstrated that myeloid cell deficiency in PKCδ indeed increase macrophage proliferation in the atherosclerotic lesion (figure) 4 . The authors could show increases in both BrdU-incorporation and Ki67-staining in PKCδ-deficient macrophages in the atherosclerotic lesion, both which are markers of proliferation.…”
supporting
confidence: 62%
“…On the contrary, selective deletion of PKCδ in myeloid cells, using LysM-Cre-mediated deletion, dramatically increased atherosclerosis 4 . The increased atherosclerosis was associated with an increase in lesional macrophage accumulation, but with no evidence of increased recruitment of monocytes into the lesion.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Apoptosis also plays a crucial role in human cardiovascular diseases, including atherosclerosis [61,62], myocardial infarction [63], and heart failure [64]. The identification of annexin V as a high-affinity ligand to apoptotic cells presented a natural opportunity to apply molecular imaging technology in imaging apoptosis in vivo.…”
Section: Imaging Of Apoptosismentioning
confidence: 99%